Design and Characterization of Herbal Transdermal Patch Containing Capsaicin Extract and Mustard Oil for Arthritis - Lokapur, Arpitha Jayatheertha; Joshi, Vedamurthy (Indian Journal of Pharmaceutical Education and Research, 2025)
Introduction Arthritis, a chronic inflammatory condition causing significant pain and diminished quality of life, affects millions worldwide. This study aimed to develop and characterize a novel herbal transdermal patch using mustard oil and capsaicin extract, extracted via water, alcohol, and mustard oil. The extracts underwent preliminary examination and were assessed for in vitro anti-inflammatory activity. Objectives The primary goal was to construct and evaluate a transdermal patch for arthritis treatment, incorporating capsaicin and mustard oil extracts. Additionally, the study aimed to assess the in vitro anti-inflammatory activity of the extracts, providing insights into their potential therapeutic efficacy. Materials and Methods Capsaicin extraction involved water, alcohol, and mustard oil methods, with subsequent evaluation of anti-inflammatory activity. The oil extract was processed into five transdermal patch formulations, integrating naproxen as a model drug. Parameters such as weight variations, folding endurance, tensile strength, and moisture content were analysed. In vitro drug permeability and ex vivo permeation tests were conducted, employing Rhodamine B/Oil Red O dye. Results The water-extracted capsaicin exhibited reduced potency on the fourteen days, with observed fungal growth. The alcohol extract showed diminished potency compared to the oil extract. The transdermal patch formulations demonstrated drug release within the range of 0.1 to 0.3 mm, 3% moisture content, 1-pascal tensile strength, and a drug release rate of 90% during in vitro and ex vivo tests, utilizing Rhodamine B/Oil Red O dye.
Keywords: Transdermal patch; Capsaicin extract; In vitro and ex vivo permeation study; Docking study; Arthritis